Exploring the nexus of gender and environment in the H2020 PHOENIX project: insights from the design of a gender equality plan - Esteves, Denise; Holz, Sheila; Lopes, Mónica; Sandri, Sinara (Frontiers in Environmental Science, 2024)
The H2020-funded PHOENIX project (2022-2025) aims to enhance democratic innovations to implement the European Green Deal (EGD) at local, regional, and national levels, focusing on key policy areas like farm-to-fork, circular economy, energy transition, and healthy soil. Despite the European Green Deal's ambitious goals for a climate-neutral Europe by 2050, it primarily emphasizes technological solutions and overlooks social vulnerabilities like gender, class, and race. In the light of the European Commission's efforts to promote gender equality in EU-funded projects through the implementation of Gender Equality Plans (GEPs), the study carried out a comprehensive literature review aimed at gaining insights into the intricate relationship between gender and the environment with a particular focus on the intersection of gender and research and innovation, especially within the context of the European Green Deal. Drawing on their experience as action researchers developing a Gender Equality Plan within the H2020 PHOENIX project, the authors emphasize the importance of gender-sensitive research in environmental projects and underscore the significance of a participatory approach in achieving effective gender change. The lack of reporting on experiences of incorporating a gender perspective has resulted in a significant knowledge gap regarding the various impacts that environmental actions can have on people's lives, based on their gender. The article endeavours to bridge this gap by achieving two main goals: highlighting the importance of gender-sensitive research in environmental projects and discussing how the gender gap is addressed in the H2020 PHOENIX project through its participatory approach to design the Gender Equality Plan.